(untitled) (Academia Journal of Medicine, 2020)
Background: Rheumatoid arthritis (RA) primarily affect the synovium and is a chronic inflammation disease, which leads to joint damage and bone destruction. Causes of significant morbidity are due to result of synovial inflammation, joint destruction and associated disability. Many pieces of evidence suggest that proatherogenic disease associated with increased cardiovascular (CV) mortality is rheumatoid arthritis (RA). Addition to genetic and conventional CV risk factors, chronic inflammation has emerged as a key component of this process. Cardiovascular concerned demises shown a preferment in CRP among RA cases who have ongoing active inflammation that’s why CRP can be self-sufficient pointer for cardiovascular disease. Subjects and Methods: Current study has been conducted in Teerthanker Mahaveer hospital, Teerthanker Mahaveer medical college. Data has been collected in duration of 12 months. After obtaining consent, data has been collected from 60 consecutive established case of rheumatoid arthritis. Almost equal number of participants were belonging to 30-39 years (16, 26.7%), 40-49 years (15, 25.0%), and 50-59 years (16, 26.7%) age groups. Very few participants were belonging to 20-29 years (4, 6.7%) and 60-69 years (9, 15.0%). Range of age was from 25 years to 69 years. Results: Pearson correlation coefficient of CPR with Total cholesterol, HDL-C, Triglyceride, LDL-C and VLDL-C were -0.326, -0.269, -0.307, -0.310 and -0.307 respectively. All the correlation coefficients were statistically significant (<0.05). Correlation coefficient of ESR with Total cholesterol, HDL-C, Triglyceride, LDL-C and VLDLC were -0.294, -0.311, -0.226, -0.253 and -0.226 respectively. Among them correlation coefficient of ESR with total cholesterol (p-value=0.023) and HDL-C (p-value=0.016) were statistically significant (<0.05). Conclusion: General population danger of atherosclerosis surmount with increment in LDL and wane of HDL but in RA population there is wear off in HDL LDL and total cholesterol, when present in its inflammatory condition. There is a difference in the lipid trend in RA patient then the general population. Rheumatoid arthritis is a disease with lipid paradox. A high inflammatory burden determined by the mean values of ESR and CRP in active disease is associated with low lipid levels but more risk of CV events.